2021
DOI: 10.1038/s41598-021-83693-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of serum hyaluronic acid levels as a predictor of incidence of hand osteoarthritis analyzed by longitudinal analysis from the Iwaki cohort

Abstract: The factors predicting hand osteoarthritis (HOA) in patients remain unknown. We aimed to investigate the usefulness of serum hyaluronic acid (sHA) levels in predicting HOA progression from a 6-year longitudinal epidemiological study. A total of 417 participants in the Iwaki cohort were followed-up over 6 years. Hand and knee radiographs taken at baseline and follow-up were scored according to Kellgren–Lawrence grades and Kallman score. Participants were classified into the HOA group and the non-HOA group. sHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, the expression level of HA in AD-MSCs group diminished significantly and the average serum level of HA among the patients who received AD-MSCs injection, decreased by 47.18% after 3 months compared with the baseline. The correlation between serum HA concentration and OA has been evidenced in numerous literatures [ 51 , 52 ]. Serum HA has been proposed as an alternative tool besides conventional diagnostic methods for early detection of KOA and monitoring the disease progression [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression level of HA in AD-MSCs group diminished significantly and the average serum level of HA among the patients who received AD-MSCs injection, decreased by 47.18% after 3 months compared with the baseline. The correlation between serum HA concentration and OA has been evidenced in numerous literatures [ 51 , 52 ]. Serum HA has been proposed as an alternative tool besides conventional diagnostic methods for early detection of KOA and monitoring the disease progression [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such inquiry may also be further elevated through use of sensitive advanced cartilage MRI methodologies including structural MRI such as isotropic 3-dimensional fast spin echo and gradient recalled echo sequences and compositional MRI techniques (transverse relaxation time mapping, delayed gadolinium-enhanced MRI of cartilage, T 1 ρ mapping, sodium MRI, and diffusion-weighted imaging) 40 . Recent work on recognition of biomarkers associated with osteoarthritic change, along with increased sophistication of imaging tools, could further enhance an early identification process for clinical utilization 41,42 . With early identification, future implementation of disease interruption or ideally prevention measures could also be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…40 Recent work on recognition of biomarkers associated with osteoarthritic change, along with increased sophistication of imaging tools, could further enhance an early identification process for clinical utilization. 41,42 With early identification, future implementation of disease interruption or ideally prevention measures could also be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of HA, as well as COMP, has been shown to be sensitive to early OA in the knee joint (Jiao et al, 2016). It has also been reported that HA was able to predict the incidence of hand OA (Saruga et al, 2021).…”
Section: Introductionmentioning
confidence: 98%